Acute Hematological Responses to a Maximal Incremental Treadmill Test - Lima, Filipe Dinato de (2017)
The present study aimed to study acute hematologic responses in individuals undergoing a  cardiopulmonary maximum incremental treadmill test without inclination. Were analyzed 23 individuals, 12 men and 11 women, with a mean age of 30.2 (± 8.4) years, mean weight of 68.1 (± 18.1) kg, mean height of 170.2 (± 9.8) cm, and mean BMI of 23.2 (±3.7) kg/m², physically active, with a minimum practice of 3.5 hours per week of exercise for at least 6 months. The subjects were submitted to a maximal incremental treadmill test, with venous blood collection for analysis before and immediately after completion of the test. Was used Wilcoxon test for analysis of pre and post test variables. Was adopted p < 0.05 as significance level. There was a significant increase in leukocyte count (69.23%; p = 0.005), lymphocytes (17.56%; p = 0.043), monocytes (85.41%; p = 0.012) and granulocytes (28.21%; p = 0.011). It was also observed a significant increase in erythrocytes (3,42%; p = 0,042), hematocrit (5.39%; p = 0.038) and hemoglobin (5.58%; p = 0.013). With this study, was concluded that performing a maximal test of treadmill running can significantly raise blood levels of leukocytes and respective sub-populations, as well as red blood cells and hemoglobin.